Construction of the Istanbul Canal by Turkey: Geopolitical Consequences for the Black Sea Region - Pavel A. Vysotsky (RUDN Journal of Political Science)
The Turkish Istanbul Canal infrastructural project is formally aimed at solving the problems related to the ecological situation in the Black Sea and its straits. The construction of the canal should create additional opportunities for the expansion of shipping, especially if cargo traffic increases. However, the new waterway, which is to pass through Turkish territory, affects not only the problems of navigation and use of water resources, but will also become a powerful catalyst for new geopolitical projects. The construction of the canal will allow Ankara to bypass the provisions of the Montreux Convention, which regulates the passage of vessels through the Bosporus and Dardanelles straits. The study analyses how the implementation of this project will affect the geopolitical situation in the Black Sea. The construction of a new water route passing through Turkish territory will strengthen Ankara’s political position in the Black Sea region. In this case, the passage of vessels through the waterway will be regulated by national legislation. The author uses historical and comparative methods to reveal the peculiarities of Turkish policy on the construction of the canal. The article concludes that the implementation of this project will strengthen Turkey’s position in the Black Sea region and enforce its role in determining geopolitical processes in the area.